Keripik Kulit Singkong sebagai Upaya Pemanfaatan Limbah Bernilai Ekonomis di UMKM Keripik Selo Gedong - Prakoso Adi; Rizka Mulyani; Citra Bherly Fantika Wibowo; Ragil Siwi Puspa Khirana; Anisa Kurniawati; Arum Puspa Maharani; Bowis Fatwa Afif; Ceut Halimah Heca Wardani; Cindy Amelia; Dea Yoana Putri Damayanti; Dewi Irawati; Hanifah Eka Cahyani; Amiwiti Fayyadh Islami Falih; Earlian Zaka Bintang Lazuardi (Universitas Sebelas Maret, 2023)
Cassava Peel Chips as an Effort to Utilize Economic Value Waste in Keripik Selo Gedong MSME. Micro Small Medium Enterprise (MSME) Selo Gedong Chips has produced various chips, including cassava, banana, and bote. The obstacle is that cassava peel waste, which reaches 20% of the total cassava produced so far, has only been used as animal feed and has not been widely used for human consumption. Even though cassava peel still has the potential to be a healthy food because its fiber content is 15.20% (w/w). However, the high content of cyanide acid (HCN) (419.8 mg/kg) and its toxic nature is a weakness so it needs to be treated to reduce the toxicity. This activity aims to process cassava peel waste into cassava peel chips with economic value. To increase the selling value of the cassava peel chips, a cassava peel chip oil drainer was provided to increase the product's shelf life and attractive packaging was introduced for the cassava peel products. Based on the results of training in making cassava peel chips, soaking in salt for three days succeeded in reducing cyanide acid levels to a concentration suitable for consumption, namely 4.32 ppm. The formulations most preferred by the panelists were the balado flour and original flour formulations. One 80-gram package of cassava peel chips can be sold for IDR 6,500.00. Judging from the evaluation aspect, the enthusiasm of the training participants in making cassava peel chips has a high score. Apart from that, looking at the skill aspect, participants were able to produce cassava peel products that were safe to consume and crunchy with attractive packaging.